DEVELOPMENT OF AHP BASED MODEL FOR DECISION MAKING ON E-LEARNING IMPLEMENTATION - Begičević, Nina; Divjak, Blaženka; Hunjak, Tihomir (Journal of Information and Organizational Sciences, 2007)
Strategic planning of e-learning implementation includes decision making about the most suitable form of implementing e-learning on different levels. Decision making about e-learning implementation has been covered as consisting of four phases: (1) intelligence, (2) design, (3) choice and (4) implementation. During the Intelligence phase we have precisely identified our central decision problem and have conducted situation analysis. In the Design phase we have developed alternatives and established criteria and subcriteria. Then, we have created the questionnaire about the importance of the advantages and goals of e-learning implementation and about criteria and subcriteria essential for decision making. The survey has been conducted on the sample of 90 elearning experts in Croatia. Further, we connected these findings with the results of the factor analysis which was performed on the complete survey. The results of the factor analysis have served as input in the multicriteria decision model (AHP) that we have developed in the Choice phase. The AHP model will be presented in the article and qualitative and quantitative evaluation of the model will be indicated.